Model Kebijakan Pendidikan Kebangsaan Bagi Mahasiswa Baru - Abdurrohman Abdurrohman; M Zainul Asror (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this research is to strengthen national insight and love for the homeland in new students in countering radicalism. The research method uses descriptive research with a qualitative approach. The results of the study show that the national education model applied to the Campus Life Program for New Students (PKKMB) is designed not with a pattern of indoctrination and upgrading but is dialogical, creative and innovative which is relevant to the character of today's millennial generation. The implementation of activities is classified into two domains; namely the scientific domain (mind) through critical-reflective scientific studies and the non-scientific domain (attitude) which contains elements of creativity, games and art. The conclusion of the study is that the national education model in order to support government policies through the National Action Plan for Combating Extremism (RAN-PE) in an effort to combat terrorism as part of the soft power approach in order to foster a sense of nationalism and love for the homeland among new students, is still a contemporary problem of nationality. Keywords: New Student, Model, National Educatio, Policy